New developments in human neurocognition: clinical, genetic, and brain imaging correlates of impulsivity and compulsivity - Fineberg, Naomi A; Chamberlain, Samuel R.; Goudriaan, Anna E.; Stein, Dan J.; Vanderschuren, Louk J. M. J.; Gillan, Claire M.; Shekar, Sameer; Gorwood, Philip A. P. M.; Voon, Valerie; Morein-Zamir, Sharon; Denys, Damiaan; Sahakian, Barbara J.; et al. (CNS spectrums, 2014)
Impulsivity and compulsivity represent useful conceptualizations that involve dissociable cognitive functions, which are mediated by neuroanatomically and neurochemically distinct components of cortico-subcortical circuitry. The constructs were historically viewed as diametrically opposed, with impulsivity being associated with risk-seeking and compulsivity with harm-avoidance. However, they are increasingly recognized to be linked by shared neuropsychological mechanisms involving dysfunctional inhibition of thoughts and behaviors. In this article, we selectively review new developments in the investigation of the neurocognition of impulsivity and compulsivity in humans, in order to advance our understanding of the pathophysiology of impulsive, compulsive, and addictive disorders and indicate new directions for research.